Plan S and cOAlition S: from principles to implementation - Rooryck; Johan [Verfasser] (My University, 2022)
2018, a group of national research funding organisations, with the support of the European Commission and the European Research Council (ERC), announced the launch of cOAlition S, an initiative to make full and immediate Open Access to research publications a reality. It is built around Plan S, which consists of one target and 10 principles. In the article Rooryck describe the Plan S Guidance, the journal checker tool which should helping the authors and the three policies for the transition to full and immediate Open Access. Furthermore, he has a deeper look to the transition of Open Access books and the activities from smaller publishers in this field. (BIBB-Doku)
Keywords: 330; Open Access; Forschungseinrichtung; Finanzierung; Initiative; Förderung